A SOLUTION PROPOSAL FOR INTERVAL SOLID TRANSPORTATION PROBLEM - Aydin, Fugen Torunbalci; Guler, Coskun; Sivri, Mustafa (YILDIZ TECHNICAL UNIV, 2006)
The solid transportation problem is often presented in the literature. Recently, the solutions of solid transportation of the goods from warehouses into markets and from warehouse into markets by any way is solved by traditional ways by complex formulas. In the present work the problem is solved with simple formulation considering transportation costs by intervals and it makes some contributions to the literature.
Keywords: Interval linear programming; transportation problem; Engineering